Transanal Ileal Pouch-Anal Anastomosis for Ulcerative Colitis has Comparable Long-Term Functional Outcomes to Transabdominal Approach: A Multicentre Comparative Study. (22nd October 2019) - Chandrasinghe, Pramodh; Carvello, Michele; Wasmann, Karin; Foppa, Caterina; Tanis, Pieter; Perry-Woodford, Zarah; Warusavitarne, Janindra; Spinelli, Antonino; Bemelman, Willem
Abstract: Background: The transanal approach to ileal pouch-anal anastomosis [Ta-IPAA] provides better access to the lower pelvis with lower short-term morbidity in ulcerative colitis [UC]. The aim of this study was to assess the long-term functional outcomes after Ta-IPAA vs transabdominal IPAA [Abd-IPAA] in UC. Methods: A multicentre cohort analysis was performed between March 2002 and September 2017. Patient characteristics, surgical details and postoperative outcomes were compared. CGQL [Cleveland global quality of life] score at 12 months with a functioning pouch was considered the primary end point. Results: A total of 374 patients [100 Ta-IPAA vs 274 Abd-IPAA] were included. Ta-IPAA demonstrated a comparable overall quality of life [CGQL score] to Abd-IPAA [0.75 ± 0.11 vs 0.71 ± 0.14; respectively, p = 0.1]. Quality of life [7.71 ± 1.17 vs 7.30 ± 1.46; p = 0.04] and energy-level items [7.16 ± 1.52 vs 6.66 ± 1.68; p = 0.03] were significantly better after Ta-IPAA, while the quality of health item was comparable [7.68 ± 1.26 vs 7.64 ± 1.44; p = 0.96]. Analysis excluding anastomotic leaks did not change the overall CGQL scores. Stool frequencies [>10/24 h: 22% vs 21%; p = 1.0] and the rate of a single episode of major incontinence during the following 12-month period [27% vs 26%; p = 0.89] were similar. The differences in 30-day morbidity rates [33% vs 41%; p = 0.2] and anastomotic leak rates were not significant [6% vs 13%; p = 0.09]. Conclusions: This study provides evidence of comparable long-term functional outcome and quality of life after Ta-IPAA and Abd-IPAA for UC.